Energy Consumption Monitoring of Solar-Powered Street Lighting Using LoRa and Fuzzy Inference System - Rozie, Fachrul; Chandra, Yudi; Suwanda, Ivan (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Street lighting is a vital infrastructure requiring efficient energy management to reduce operational costs and environmental impact. The use of Internet of Things (IoT) technology like Long Range (LoRa) in energy monitoring systems for street lighting offers a solution for real-time monitoring and control of energy consumption with low cost and wide coverage. This research aims to develop and implement an energy consumption monitoring system for street lighting using LoRa technology, evaluating system performance in terms of monitoring accuracy, reliability, and energy efficiency. The research stages include literature review, system design, hardware and software development, as well as testing and validation. The system is tested in a controlled environment to ensure accuracy and reliability. Data analysis is conducted to identify energy consumption patterns and potential savings. Results show that the voltage of the solar panel system increases during the day with sunlight intensity, while current is utilized as the lights turn on towards the evening. At 19:30, maximum power consumption is within the ideal range, with voltage gradually decreasing as the lights are used. MATLAB analysis reveals a normal energy efficiency value of 50% for the system.Lampu Penerangan Jalan merupakan infrastruktur vital yang memerlukan energi pengelolaan yang efisien untuk mengurangi biaya operasional dan dampak lingkungan. Penggunaan teknologi Internet of Things (IoT) seperti Long Range (LoRa) pada sistem pemantauan energi LPJU menawarkan solusi pemantauan dan pengendalian konsumsi energi secara real-time dengan biaya rendah dan jangkauan luas. Penelitian ini bertujuan dan mengembangkan sistem pemantauan konsumsi energi LPJU menggunakan LoRa, serta menghasilkan sistem kinerja dalam hal pengukuran, pelaporan, dan efisiensi energi. Tahapan penelitian meliputi studi literatur, perancangan sistem, pengembangan perangkat keras dan lunak, serta pengujian dan validasi. Sistem ini diuji di lingkungan terkendali untuk memastikan akurasi dan resolusi. Analisis data dilakukan untuk mengidentifikasi pola konsumsi energi dan penghematan. Hasil penelitian menunjukkan bahwa tegangan sistem panel surya meningkat pada siang hari seiring intensitas sinar matahari, sementara arus digunakan saat lampu menyala menjelang malam. Pada pukul 19.30, konsumsi daya maksimum berada dalam kisaran ideal, dan tegangan menurun seiring penggunaan lampu. Analisis data menggunakan MATLAB menunjukkan nilai efisiensi daya normal sistem ini adalah 50%.